Differential updating and morality: Is the way offenders learn from police detection associated with their personal morals? - Kaiser, Florian (European journal of criminology, 2023)
The majority of differential deterrability research has investigated whether people differ in the extent to which a perceived threat of sanctions deters them from committing a crime. Less is known about the differential influence of criminal justice intervention on sanction threat perceptions. According to deterrence theory, however, for justice intervention to successfully deter crime, a process of perceptual updating is required. In the current study, we used panel data from German adolescents to supplement the research on differential updating. We applied fixed effects regressions to analyze whether people with weaker or stronger morals update their perceptions of detection risk differently following experiences of police detection. Our findings suggest that they do: risk perceptions increased more in adolescents with weak morals than in adolescents with strong morals when they experienced a higher certainty of detection (a higher detection rate). Combined with previous findings on differential deterrence (by personal morality), our results indicate that deterrence processes may?for individuals with weak morals?play a more critical role in the prevention of crime than previous nondifferential research has suggested.